FORMATION OF SCIENTIFIC-EDUCATIONAL CLUSTERS AS AN ESSENTIAL ELEMENT OF DEVELOPMENT STRATEGY OF THE tATARSTAN REPUBLIC EDUCATIONAL SYSTEM - A. V. Timiryasova (Russian Journal of Economics and Law)
The article views the mechanisms of formation of a system of education and science integration with the industrial sector; analyzes the directions of education system development in Tatarstan with detailed description of the experience of forming the sector educational clusters as essential constituents of reforming of the Republic educational system.